Research on Scaffolding Instruction Strategies for English Writing Teaching of Rural Junior Middle School Students in China - Ma, Xiulin; Jiang, Xue; Jia, Yujuan; Wu, Tong; Nie, Zhinie (Advances in Social Sciences Research Journal, 2022)
In the teaching process of English composition writing of rural junior middle school students, there are some common cases that students "don't know how to start, the composition structure is not clear, the vocabulary sentence pattern is scanty and improper ". In view of these problems in teaching, this paper introduces scaffolding teaching strategy, designs the vocabulary sentence structure, writing frame, online interactive frame and other strategies to assist students in English writing based on the practice of English writing teaching. Through scaffolding teaching practice, the strategy and process of applying teaching scaffold to specific learning situation are explored. The results show that :(1) Scaffolding teaching ability can improve the English writing level of rural junior high school students, but also improve the learning interest of English writing in the process of learning;(2) Scaffolding teaching should not only pay attention to the process of knowledge construction, but also pay attention to the cultivation of students' interest in English learning to promote the development of learners' English writing ability.